Faktor-Faktor Yang Mempengaruhi Alih Fungsi Lahan Karet Menjadi Kelapa Sawit Di Desa Tebing Tanjung Selamat, Kec. Padang Panjang, Kab. Langkat, Prov. Sumatra Utara - M.Y, Febrian; Alham, Fiddini; Mahyudin, Thursina (Jurnal Penelitian Agrisamudra, 2024)
The purpose of this study was to analyze the effect of commodity prices, rubber age and productivity on the conversion of rubber land to oil palm plantations. The sample in this study was 38 people. The data analysis technique used multiple linear regression analysis with the regression equation Y = 3.617 + 0.087X1 + 0.437X2 + 0.268X3. Commodity prices have a significant effect on the conversion of rubber land to oil palm plantations in Tebing Tanjung Selamat Village, Padang Tualang District, Langkat Regency. This can be seen from the t sig. value of 0.042 <0.05. Rubber age has a significant effect on the conversion of rubber land to oil palm plantations in Tebing Tanjung Selamat Village, Padang Tualang District, Langkat Regency. This can be seen from the t sig. value of 0.036 <0.05. Productivity has a significant effect on the conversion of rubber land to oil palm plantations in Tebing Tanjung Selamat Village, Padang Tualang District, Langkat Regency. This can be seen from the t sig. value. of 0.049 < 0.05.